Identification and stability analysis of critical ecological land: Case study of a hilly county in southern China - Xinyi Huang; Yingcong Ye; Xiaomin Zhao; Xi Guo; Hui Ding (Ecological Indicators, 2022)
Critical ecological land is indispensable for ecosystem stability, ecosystem service provision, and ecosystem function. Assessing and monitoring the stability of critical ecological land is an effective strategy of ensuring regional ecological security. The present study focused on Xinfeng County, China, a southern hilly region, as the study area, and evaluated water conservation, soil and water conservation, biodiversity conservation, leisure and sightseeing functions, in addition to land use status, in 2000, 2010, and 2020. Afterward, ecological ecosystem service function was evaluated to identify critical ecological land. A complex network method was used to analyze ecological network stability to more comprehensively analyze characteristics of critical ecological land in time and space. According to the results, the landscape types of critical ecological land in 2000, 2010, and 2020 were primarily forest land and grassland, with the majority being forest land with high vegetation density and cover, validating the accuracy and feasibility of our method. Under the “random attack” scenario, the robustness of network connectivity in 2000, 2010, and 2020 had a consistent decreasing trend. However, under the “intentional attack” scenario, connectivity robustness changes more intense in 2010 and 2020, and the ecological network in 2020 shows instability and fragility. Additionally, according to the spatial distribution characteristics of critical ecological land, a network protection strategy is put forward to guide and support subsequent ecological protection work.